A Theory for the Surface Induced Growth of Helium Gas Bubbles in Irradiated and Annealed Copper - Boron Alloys - Tiwari, G. P.; Laghate, M.; Mehrotra, R. S. (Diffusion Fundamentals, 2017)
Neutron irradiated copper-boron alloys are employed to study the mutual interaction between metallic crystalline lattices and inert gases. Inert gases precipitate to form gas bubbles and their growth induces dilation of the matrix. This dilation, technically designated as swelling, affects the structural integrity of nuclear fuels during their service. The estimated enthalpy of solution of helium in copper is 5.5 eV/atom. As a Consequence, its solubility in the copper matrix is extremely poor and it cannot enter a copper based matrix via any thermo-chemical route. Hence, recourse to a nuclear reaction is taken to impregnate copper with helium. Helium is produced in situ through neutron irradiation in copper-boron alloys as a result of (n, alpha) nuclear reaction between boron atoms and neutrons. The characteristic feature of the growth of helium gas bubbles driven by isothermal annealing of the metallic matrix is that their rate of growth is highly sensitive to the distance of the bubbles from the external surface of the specimen. The growth of gas bubbles as a function of time and temperature is modulated by the flow of vacancies from the free surface of the specimen. A theory for the surface induced growth of helium gas bubbles in the neutron irradiated copper-boron alloys is presented here.